Early Impairment of Synaptic and Intrinsic Excitability in Mice Expressing ALS/Dementia-Linked Mutant UBQLN2 - Radzicki, Daniel; Liu, Erdong; Deng, Han-Xiang; Siddique, Teepu; Martina, Marco (Frontiers in Cellular Neuroscience, 2016)
Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are believed to represent the different outcomes of a common pathogenic mechanism. However, while researchers have intensely studied the involvement of motor neurons in the ALS/FTD syndrome, very little is known about the function of hippocampal neurons, although this area is critical for memory and other cognitive functions. We investigated the electrophysiological properties of CA1 pyramidal cells in slices from 1 month-old UBQLN2P497H mice, a recently generated model of ALS/FTD that shows heavy depositions of ubiquilin2-positive aggregates in this brain region. We found that, compared to wild-type mice, cells from UBQLN2P497H mice were hypo-excitable. The amplitude of the glutamatergic currents elicited by afferent fiber stimulation was reduced by ~50%, but no change was detected in paired-pulse plasticity. The maximum firing frequency in response to depolarizing current injection was reduced by ~30%; the fast and afterhyperpolarization in response to a range of depolarizations was reduced by almost 10 mV; the maximum slow afterhyperpolarization was also significantly decreased, likely in consequence of the decreased number of spikes. Finally, the action potential upstroke was blunted and the threshold depolarized compared to controls. Thus, synaptic and intrinsic excitability are both impaired in CA1 pyramidal cells of UBQLN2P497H mice, likely constituting a cellular mechanism for the cognitive impairments. Because these alterations are detectable before the establishment of overt pathology, we hypothesize that they may affect the further course of the disease.